GENERATOR ON ARCADYEV-MARX SCHEME WITH PEAKING OF THE PULSE FRONT IN ITS CASCADES FOR FOOD DISINFECTING - N. I. Boyko (National Technical University "Kharkiv Polytechnic Institute", 2017)
Purpose. To obtain experimentally that the duration of the high-voltage pulse front is less than 1.5 nanoseconds on the load of a pulse voltage generator of less than 50 ohms in the form of more than two working chambers with a water-containing product. That increases the efficiency of disinfection of treated products. Methodology. To obtain high-voltage pulses in working chambers - the generator load - the pulse generation method was used according to the Arkadyev-Marx scheme. The pulses on the load were measured with a low-ohm resistive voltage divider, transmitted over a broadband coaxial cable, and recorded using a C7-19 oscilloscope with a 5 GHz bandwidth. The working chambers were filled with water and consisted of an annular body made of PTFE 4 and metal electrodes forming the bottom and the chamber cover having flat linings of food stainless steel for contact with the food product inside the chamber. Results. The high-voltage pulses on the generator load of about 50 Ohm or less have a trapezoidal shape with a rounded apex and a base duration of no more than 80 ns. The experimentally obtained pulse amplitudes on the generator load are up to 18 kV. As the load resistance decreases, the amplitude of the pulses decreases, and the duration of the front and pulse duration in general are shortened because of the accelerated discharge of cascade capacitive storages. Originality. For the first time we have obtained experimentally on the load of the generator in the form of three parallel working chambers with water, the active resistance of each of which is less than 50 Ohm, the pulse front duration tf≈1 ns. In addition, we have obtained experimentally a stable 9-10 channel triggering mode of the trigatron type spark gap in a five-cascade pulse voltage generator with a step-by-step peaking (exacerbation) of the pulse front in its cascades (GPVCP). Practical value. We have obtained experimentally the nanosecond pulse front duration on the GPVCP load and that opens the prospect of industrial application of such generators for microbiologically disinfecting treatment (inactivation of microorganisms in food) water-containing food products.